Use of Standardized Assessments and Online Resources in Stroke Rehabilitation - Susan H. Lin; Pamela R. Bosch; Veronica T. Rowe; Susan E. Fasoli; Jeanne Langan (Scholarworks @ WMU, 2019)
Background: The extent to which movement-related standardized assessments and online resources are used in stroke rehabilitation is unclear in the United States. Method: The researchers used a cross-sectional descriptive survey that examined (a) therapists use of movement-related standardized assessments, (b) factors influencing learning of new assessments, and (c) use of frequency of online resources by occupational therapists and physical therapists in the United States. Results: Of 151 respondents (46.4% occupational therapists, 53.6% physical therapists), the most frequently used movement-related assessments by occupational and physical therapists were the Berg and Fugl-Meyer Assessment, respectively. More physical therapists use motor-related standardized assessments regularly than occupational therapists, and physical therapists showed more consensus among standardized assessments. Both professions cited quality of patient care for motivating them to integrate outcome measures into practice. Most therapists in stroke rehabilitation used online resources to access movement-related standardized assessment content at least 25% of the time. The Rehabilitation Measures Database was the most frequently used website. Conclusion: Both occupational and physical therapists use online resources for movement-related standardized assessments on a regular basis. However, occupational therapists do not use standardized assessments as frequently as physical therapists. A systematic study of factors that impact the integration of standardized assessments is needed to further identify barriers and inform clinical practice change.